2001
DOI: 10.1192/bjp.178.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance personnel and critical incidents

Abstract: The mental health and emotional well-being of ambulance personnel appear to be compromised by accident and emergency work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
144
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(172 citation statements)
references
References 26 publications
(28 reference statements)
12
144
0
16
Order By: Relevance
“…These stressors can have long-term psychophysical and behavioural effects on the health of firefighters, for example, anxiety and depression (Brough 2004); burnout (Prati et al 2011;Vaulerin et al 2016); emotional exhaustion (Smith et al 2003); depersonalisation (Alexander and Klien 2001); and post-traumatic stress disorder (McFarlane and Bryant 2007).…”
mentioning
confidence: 99%
“…These stressors can have long-term psychophysical and behavioural effects on the health of firefighters, for example, anxiety and depression (Brough 2004); burnout (Prati et al 2011;Vaulerin et al 2016); emotional exhaustion (Smith et al 2003); depersonalisation (Alexander and Klien 2001); and post-traumatic stress disorder (McFarlane and Bryant 2007).…”
mentioning
confidence: 99%
“…In a recent study among Swedish healthcare personnel, about 30% scored high in EE, and about 14% scored high in DP (Åhlin, Ericson-Lidman, Norberg, & Strandberg, 2015). Among ambulance service personnel in Scotland, 25% scored high in EE (Alexander & Klein, 2001). The levels of both EE and DP in our study were also lower than in a similar study among police personnel in Sweden, where 28% of the personnel reported high scores in EE and 56% of the personnel reported high scores in DP (Backteman-Erlanson et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Yet the results from the unconditional growth model showed that the mean hardiness score at the start of the training program was 1.57 (see Model 2 in Table 1 The question of whether hardiness can be developed or is a more enduring and stable personality style is not only of theoretical interest, but could be of great practical importance as well. A multitude of studies have shown that hardiness represents an important quality in individuals' mastering of challenging crisis situations (Alexander & Klein, 2001;Andrew et al, 2008;Bartone et al, 1989). This is particularly important for officers who have leadership responsibilities in combat, where their decisions and actions may represent a matter of life or death for people involved.…”
Section: Discussionmentioning
confidence: 99%